Implementasi Pengabdian Masyarakat Melalui Klinik Publikasi Ilmiah pada Jurnal Nasional bagi Guru di SMA Negeri 2 Kuala Mandor B Kabupaten Kuburaya - Syamsuri Syamsuri; Nuraini Asriati; Junaidi H. Matsum; Herkulana Herkulana; Achmadi Achmadi; Khosmas Khosmas (Jurnal Pengabdian UNDIKMA, 2022)
This service activity aims to educate partners about national journals and procedures for submitting manuscripts until they are published in national journals. The method of this activity was clinical or practiced. This service activity was attended by 20 teachers of SMAN 2 Kuala Mandor B, Kuburaya Regency. The instruments of the research were pre-test, post-test, and clinical performance. The data analysis technique was carried out by comparing the pre-test and post-test results. The results of this service indicated that the increase in teacher understanding included (1) teachers had understood the stages in scientific publications, (2) the teachers understood how to submit manuscripts to a national journal, and (3) the teachers understood how to find national journals according to their targets and needs. Thus, this service activity implies that it can increase knowledge, experience, and skills that are pretty good on partners' competence in supporting their careers as professional teachers.